1999
DOI: 10.1161/01.str.30.11.2440
|View full text |Cite
|
Sign up to set email alerts
|

Serial Magnetic Resonance Imaging of Rat Brain After Induction of Renal Hypertension

Abstract: Background and Purpose-Hypertension is a major risk factor for ischemic and hemorrhagic stroke and may also cause more chronic and subtle brain injury. Progressive brain changes in a rat model of renal hypertension have been assessed to better understand the pathogenesis of hypertensive brain damage. Methods-Young adult rats were made hypertensive by partial occlusion of both renal arteries. MR images of brain were obtained weekly, and histopathological outcome was assessed. A separate group of rats was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…To test whether these differences in AMPA vulnerability are strictly caused by inherent genetic differences between SHRs and WKYs or related to the level of MAP, we used the model of nongenetic hypertension, induced by renal artery stenosis in rats. 16 This model provides further evidence that the level of MAP per se is not at the origin of the aggravation of the lesion induced by intracerebral AMPA administration. This specific vulnerability to AMPA but not to NMDA in SHRs is also consistent with previous neuroprotective studies in SHRs in which several AMPA receptors antagonists were efficient in terms of a significant decrease in ischemic brain damage, whereas NMDA receptor antagonists failed to protect the brain against ischemic injury in SHRs compared with normotensive rats.…”
Section: Lecrux Et Al Excitotoxic Brain Lesions In Hypertensive Rats mentioning
confidence: 59%
“…To test whether these differences in AMPA vulnerability are strictly caused by inherent genetic differences between SHRs and WKYs or related to the level of MAP, we used the model of nongenetic hypertension, induced by renal artery stenosis in rats. 16 This model provides further evidence that the level of MAP per se is not at the origin of the aggravation of the lesion induced by intracerebral AMPA administration. This specific vulnerability to AMPA but not to NMDA in SHRs is also consistent with previous neuroprotective studies in SHRs in which several AMPA receptors antagonists were efficient in terms of a significant decrease in ischemic brain damage, whereas NMDA receptor antagonists failed to protect the brain against ischemic injury in SHRs compared with normotensive rats.…”
Section: Lecrux Et Al Excitotoxic Brain Lesions In Hypertensive Rats mentioning
confidence: 59%
“…Indeed, we have previously shown that 7-week-old SHR, in which hypertension is not yet established, also exhibit exacerbated ischemic brain damage when compared with agematched WKY (Lecrux et al, 2007). On the basis of these observations, we have used another wellcharacterized model of nongenetic hypertension, induced by renal artery stenosis in WKY (Del Bigio et al, 1999). In those animals, arterial pressure increased after stenosis and reached a plateau after 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…All the animals were subjected to ischemia 3 months after the induction of hypertension. At this time, it is known that hypertension induces structural (thickening of small artery walls, altered vasodilatation (Li et al, 1996;Del Bigio et al, 1999;Stankevicius et al, 2002)) and functional alterations of the cerebral circulation (e.g., shift of the lower limit of cerebral blood flow autoregulation) similar 2.0±1.3 6.6±3.9 -0.5±3.3 -1.0±2.5 -0.5±2.4 4.3±1.5 Figure 5 Representative perfusion-diffusion mismatch in a WKY, SHR, and RH-WKY rat at 90 minutes after occlusion. The blue color indicates abnormal diffusion area, whereas the red color indicates the ischemic penumbra as defined by perfusion-diffusion mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies in persons with chronic hypertension have revealed greater numbers of subcortical white matter lesions and microinfarcts, astrogliosis, ventricular enlargement, and extracellular fluid accumulation than in agematched controls. [275][276][277][278][279][280][281][282][283][284][285] Mild cognitive impairment (MCI) is a diagnostic category that represents a transitional state between normal aging and mild dementia in which patients exhibit signs of poor recent memory but can still perform daily tasks such as managing finances, driving, shopping, and preparing meals. 286 Hypertension and hypercholesterolemia are risk factors for MCI and for other signs of cognitive decline, such as impaired attention, reaction time, verbal fluency, or executive function.…”
Section: Cognitive Function and Dementiamentioning
confidence: 99%